Minimum amount of time required to retrieve peripheral numeric information in augmented-reality systems using a colour sequential DLP display - Menozzi, Marino; Bergande, Esther; Bonan, Jutta; Sury, Philipp; Krueger, Helmut (Displays, 2007)
In a typical environment for augmented reality, subjects were asked to detect visual information presented at 15–28° in the periphery of the visual field. Information was displayed tachistoscopically for 200, 300 and 600 ms. Popular low cost beamer producing colour breakup was used to present peripheral stimuli. We found that exposure time affects detectability of targets. By extrapolating our results we compute that for a 100% correct detection the stimulus must be displayed for at least 2 s. Age does not affect detectability.